JAK2 exon 12 variants in vietnamese patients with JAK2 V617F-negative primary myelofibrosis - Thy Ngoc, Nguyen; Manh Quyet, Ha (Vietnam Journal of Biotechnology, 2023)
Primary myelofibrosis is the severe form of myeloproliferative neoplasms that causes scar tissue in the bone marrow, leading to low production of blood cells and thus, life span shortening. Besides the most common variant JAK2 V617F, the association between these disorders with other variants in the JAK2 gene, especially the exon 12 variants have been poorly studied. In our research, the JAK2 exon 12 variants were detected by amplification and sequencing from genomic samples of five cases with V617F-negative primary myelofibrosis. Results showed that among 5/14 primary myelofibrosis patients with V617F-negative profile, only two patients carried exon 12 variants (JAK2 c.1592A>G p.H531R, and c.1613A>C p.H538P). In silico analysis indicated that the variant c.1613A>C p.H538P was novel and potentially pathogenic. The positioning demonstration by Missense3D tools indicated that this variant localized in the proximity to the pathogenic variant V617F, suggesting a potential effect on the enzymatic activity of Janus kinase 2. This initial data can be used as a genetic diagnostic criterion for myeloproliferative neoplasms. Nonetheless, the effect of p.H538P needs to be verified by further investigations.